The Strategy Of The Regional Disaster Management Agency (BPBD) Of Dki Jakarta In Enhancing Flood Disaster Risk Reduction Efforts To Support National Security - Faiz Damayanti; Sobar Sutisna; Ali Rahmat; Wilopo Wilopo (CV. AFDIFAL MAJU BERKAH, 2026)
Indonesia, as an archipelagic nation, is highly vulnerable to hydrometeorological disasters, particularly flooding, which poses significant social, economic, physical, and environmental risks. Jakarta, with its low-lying topography and traversed by 13 river estuaries, is categorized as a medium-level disaster risk area with a risk index of 61.31 in 2023. The coastal region of North Jakarta, affected by land subsidence, reclamation, and mangrove degradation, is especially prone to tidal flooding, with severe impacts on local communities. This study aims to analyze the role of the Jakarta Regional Disaster Management Agency in enhancing flood disaster risk reduction as part of efforts to support national security. Using a literature review and descriptive research approach, the study examines Jakarta Regional Distaster Management Agency’s disaster management strategies based on the disaster management cycle, including prevention through diversion channels, dams, and water pumps; preparedness with early warning systems, evacuation facilities, and public education; response involving rescue operations, humanitarian aid, and community mobilization; and rehabilitation and reconstruction focusing on restoring infrastructure, public services, and socio-economic recovery. The findings indicate that BPBD plays a crucial role in strengthening community resilience, minimizing disaster impacts, and integrating disaster risk reduction into long-term development planning. These efforts not only mitigate flood risks but also contribute significantly to maintaining national security in the capital region.